2007
DOI: 10.1177/1049909107302304
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Suffering State Examination Scale: Possible Key Criterion for 6-Month Survival and Mortality of Critically Ill Dementia Patients

Abstract: Six months of survival as a key criterion is extremely important for decision making in enrollment of critically ill patients to palliative settings. This was a prospective cohort study with 6 months of follow-up during a 24-month period performed in the Division of Geriatric Medicine in a tertiary general hospital. One-hundred three consecutively admitted, bedridden patients with end-stage dementia were evaluated. The Mini-Suffering State Examination scale was performed. Interrelations between the Mini-Suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
0
30
2
Order By: Relevance
“…Compared to the ADEPT scale, Mitchell et al 16 found the US Medicare hospice eligibility guidelines to have poor discrimination. Aminoff 11 found the MSSE scale to be particularly associated with increased mortality within 6 months, and previous studies have reported MMSE to have high specificity, but low sensitivity, especially with non-Alzheimer dementias. 30 …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Compared to the ADEPT scale, Mitchell et al 16 found the US Medicare hospice eligibility guidelines to have poor discrimination. Aminoff 11 found the MSSE scale to be particularly associated with increased mortality within 6 months, and previous studies have reported MMSE to have high specificity, but low sensitivity, especially with non-Alzheimer dementias. 30 …”
Section: Discussionmentioning
confidence: 91%
“…11,12 Mitchell et al 15 found that decreased activities of daily living scores were strongly and significantly associated with increased mortality. A definition of “not awake most of the day” was also identified as an associated risk factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of our clinical study demonstrated that the intense suffering level of patients evaluated by a recently developed objective tool, the Mini-Suffering State Examination (MSSE) scale, has a significant correlation with short survival [16], advancing age, more severe illness, malnutrition, the existence of decubitus ulcers, and the administration of medications [17].…”
Section: Discussionmentioning
confidence: 96%
“…1,[24][25][26][27][28] Instead, the cause of death is listed as pneumonia, difficulty swallowing, or failure to thrive, which are all common complications of AD. 1,18,29 This lack of accuracy in reporting deaths from AD may lead to a misperception that AD is not a terminal illness, which thus may prevent patients and families from making informed end-of-life (EOL) choices. 25 …”
Section: Alzheimer Diseasementioning
confidence: 99%